Implementasi Sistem Informasi Akuntansi pada BUMDes Dwi Amertha Sari Desa Jinengdalem - Rahayu, Putu Medina; Julianto, I Putu (Universitas Pendidikan Ganesha, 2021)
This study was aimed to gain an understanding of the implementation of accounting information systems in BUMDes Dwi Amertha Sari Jinengdalem, Buleleng District, Buleleng Regency. This study uses a qualitative method. Data collection is done by means of observation, interviews, and study documentation. The results of this study indicate that the BUMDes was formed as a means to assist the community in meeting their needs with the payment of clean water and savings and loans to the community. With the presence of BUMDes Dwi Amertha Sari, people get the convenience of business units in BUMDes, and also BUMDes can provide benefits in public services. The application of accounting information systems in Jinengdalem Village with the application of Sedana Dimata and PAMS Meter is able to be the main driver of the development of information technology that is easy to use. In this application has the advantage of data security that is maintained and accurate for business. With the appearance of the use of modern technology so that it can be used by users and is ready for use anytime.